Evaluating a commercial inertial measurement unit system for quantifying biomechanical joint angles during ice hockey shooting tasks - Iizuka, M.; Wilkie, E. W. C.; Denroche, S. K.; Renaud, P. J.; Pearsall, D. J.; Robbins, S. M. (Sports Engineering, 2026)
This study compared inertial measurement unit and optoelectric motion capture systems to measure joint kinematics during ice hockey shooting tasks. Eight high-level male players performed ten static wrist shots and slap shots on an in-lab artificial ice surface, recording data concurrently with both systems. Root Mean Square Error and the Coefficient of Multiple Correlation were used to quantify the differences and similarities in the participant`s joint angle measures between the two systems. Across all joints, average errors were comparable about the sagittal and frontal plane (within 12°), though transverse plane errors were higher. Similarity measures about the sagittal, frontal, and transverse planes indicated very good (0.91), good (0.78-0.80), and moderate (0.70-0.74) waveform similarity, respectively. The relative errors observed were predominantly attributed to biomechanical model differences within each technology. Hence, future research should focus on standardizing models and calibration procedures and investigate longer, more complex tasks. Given the good to moderate agreement in the sagittal and frontal planes` absolute measures and measures over time, but poor agreement in transverse plane joint angles and frontal/transverse shoulder joint angles, caution should be taken when comparing hockey studies that use different motion capture systems for certain joints. Ankle (sagittal), knee (sagittal), and hip (frontal) inertial measurement unit joint angles provide valid data for ice hockey contexts as their errors are less than group comparison differences found in other studies. Inertial measurement units may provide a balanced option between practicality and accuracy to quantify representative and real time movement technique of ice hockey shooting.